2009
DOI: 10.2355/isijinternational.49.788
|View full text |Cite
|
Sign up to set email alerts
|

Wetting of Solid Iron, Nickel and Platinum by Liquid MnO–SiO2 and CaO–Al2O3–SiO2

Abstract: Wetting of solid metals-iron, nickel and platinum, by molten MnO-SiO 2 (MS) and CaO-Al 2 O 3 -SiO 2 (CAS) oxide systems was studied by the sessile drop method at 1 350-1 450°C in reducing atmosphere. Terminal contact angles (after 240 min) for MS system were: for iron substrates-5Ϯ2 deg at 1 350°C, 9Ϯ2 deg at 1 390°C, 6Ϯ2 deg at 1 450°C; platinum-15Ϯ2 deg at 1 350°C and 1 390°C, and 12Ϯ2 deg at 1 450°C. Contact angle for the Ni-MS system was close to zero-3Ϯ2 deg at 1 350°C and 1 390°C. Contact angles with CAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The large SiO 2 -MnO-Al 2 O 3 inclusion that demonstrated in irregular plate strip is up to nearly 372 µm. In general, the SiO 2 -MnO-Al 2 O 3 type inclusions considered as easily deformable have a low liquidus temperature and contact angle, which could increase difficulties of the removal by its floatation [31][32][33]. Besides, large-size inclusions, e.g., SiO 2 -MnO-Al 2 O 3 , CaO-SiO 2 -Al 2 O 3 inclusions with low contact angles were also considered to have a poor tendency of agglomeration [34].…”
Section: Analysis Of Defective Part On the Ingotmentioning
confidence: 99%
See 2 more Smart Citations
“…The large SiO 2 -MnO-Al 2 O 3 inclusion that demonstrated in irregular plate strip is up to nearly 372 µm. In general, the SiO 2 -MnO-Al 2 O 3 type inclusions considered as easily deformable have a low liquidus temperature and contact angle, which could increase difficulties of the removal by its floatation [31][32][33]. Besides, large-size inclusions, e.g., SiO 2 -MnO-Al 2 O 3 , CaO-SiO 2 -Al 2 O 3 inclusions with low contact angles were also considered to have a poor tendency of agglomeration [34].…”
Section: Analysis Of Defective Part On the Ingotmentioning
confidence: 99%
“…In the meanwhile, a few CaO content appeared in some SiO 2 -MnO-Al 2 O 3 inclusions, and the shapes changed from sphere to non-smooth and irregular sphere. After the addition of Si-Al complex deoxidizer during the following LF1 and LF2 refining process, the main inclusions converted into CaO-SiO 2 -Al 2 O 3 type with a low liquidus temperature and contact angle as well [31,34]. Additionally, only a few SiO 2 -MnO-Al 2 O 3 inclusions with decreasing sizes were found at the end of the LF2 refining process.…”
Section: Characteristics Of the Inclusions During The Metallurgical P...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the oxidation of metal can be effectively prevented by adding 5 vol% H 2 in Ar gas [14,15] . In the current study, the volume percent of H 2 in Ar gas was adjusted from 0% to 5% to change oxygen partial pressures.…”
Section: Effect Of Oxygen Partial Pressurementioning
confidence: 99%
“…Obviously, graphite as a substrate can only be used in a reducing atmosphere and may react with the oxide system [14,21]. The wetting of platinum by the MnO-SiO 2 and CaO-AI 2 O 3 -SiO 2 oxide system was analyzed in [22], where oxide reduction and the dissolution of Mn into the substrate occurred, and the reaction at the phase interface promoted wetting, resulting in dynamic wetting behavior. In the case of the graphite substrate, the absence or minimal wetting by molten oxide mixtures is due to the weak van der Waals forces underlying interfacial bonding [23].…”
Section: Introductionmentioning
confidence: 99%